Simulations of heat transfer in a boundary layer subject to free-stream turbulence - Li, Qiang; Schlatter, Philipp; Henningson, Dan S. (6th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2009, 2009)
The ptesenl study investigates the effects or the ambient, free-stream turbulence (FST) on the momentum and heat transfer in a turbulent flat-plate boundary layer via large-eddy simulations (LES) using the ADM-RT model. Due to a FST of 20%, the skin-friction coefficient c/and Stanton number St are substantially elevated up to 15% in the fully turbulent region. The depression of both the mean velocity and temperature profiles in the wake region due to the FST is observed, however, the influence on the wall-normal heat flux in the near-wall region is negligible.
CRIS-Team Scopus Importer:2023-03-21